Using of Ethno-STEM Based Teaching Materials to Increase the Creativity of Students in Learning Physics - Nuning Rohmantika; Eko Setyadi Kurniawan (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2021)
21st-century education requires creative students who can master science and technology, art, and culture through the development of education. Innovation in physics learning is needed to increase the creativity of students in the 21st century. One of the efforts to support the creativity of students is through the integration of STEM learning combined with local wisdom. Ethno-STEM is an educational approach that is appropriate to be applied in the 21st century. The integration of STEM and Ethnoscience approaches can make physics learning more meaningful. The research was conducted to determine the use of Ethno-STEM-based teaching materials in increasing the creativity of students in physics learning with the subject of dynamic fluid. The research method used is the pre-experimental method with a one-group pre-test and post-test design. Data were collected through observation sheets and creativity test instruments. Analysis of research data obtained by calculating N-Gain, normality test, and paired t-test. The results of the N-Gain calculation obtained a value of 0.50 in the medium category. The results of the paired t-test obtained a significant difference between the pre-test and post-test. The results of the research indicate that using Ethno-STEM-based teaching materials can increase students' creativity in learning physics.